Frequency and Prognosis of Epidermal Growth Factor Receptor Variant III Mutations in Glioblastoma Multiforme among Indian Patients: A Single-Institution Study - Jose, Wesley Mannirathil; Munirathnam, Vinayak; Narendranath, V.; Philip, Arun; Keechilat, Pavithran (South Asian Journal of Cancer, 2020)
Background Glioblastoma multiforme (GBM) is a disease with poor outcome. Alterations or mutations in epidermal growth factor receptors (EGFRs) are found in GBM and may be targeted to improve outcomes.Aims We analyzed the frequency of EGFR variant III (vIII) mutations in patients with GBM and their outcomes after standard treatment.Materials and Methods This is a retrospective study conducted in a single tertiary cancer center in south India. Forty patients with GBM who had their entire treatment done at this center were identified, and their primary tumor tissue blocks were retrieved. Genomic DNA was extracted, and molecular analysis was performed and analyzed. The results of mutational analysis were correlated with treatment outcome of the patients.Statistical Analysis Survival outcome was analyzed using the Kaplan–Meier method. The log-rank test was used to assess the association between the groups and various parameters.Results Our study showed a similar incidence of EGFR vIII alterations as published in world literature, but we did not find any difference in overall survival (OS) and progression-free survival (PFS) in patients with EGFR vIII mutation compared with nonmutant cohort.Conclusions Contrary to the existing literature which indicated EGFR vIII alterations to be a negative prognostic indicator, our study did not find it to be an independent predictor of prognosis among Indian GBM patients treated with present standard of care.
Keywords: epidermal growth factor receptor; glioblastoma multiforme; mutation; variant III